The genus Issikiopteryx (Lepidoptera: Lecithoceridae): Checklist and descriptions of new species - Fan, Ximei; Li, Houhun (Zootaxa, 2008)
Thirteen species of the genus Issikiopteryx are listed on a worldwide basis. Three new species, Issikiopteryx obtusangula sp. nov., I. rotundiconcava sp. nov. and I. valvispinata sp. nov. are described based on the examination of the specimens collected from China. Five species, Glaucolychna fornicata Wu & Liu, G. aurolaxa Wu & Liu, G. corona Wu & Liu, G. ophrysa Wu & Liu and G. trichacera Wu, are transferred to Issikiopteryx. Images of the adults and the genitalia of the new species are provided.